Dynamics of business cycle synchronization within Turkey - Hasan Engin Duran (Turkish Economic Association, 2015)
The aim of the present article is to investigate the economic determinants of the synchronization across regional business cycles in Turkey between 1975-2010. The vast majority of studies in this field have concentrated on well known determinants, such as interregional trade, financial integration and industrial specialization, while largely ignoring spatial and geographical factors including differences across regions in agglomeration, localization economies, market size and urbanization In this article, we incorporate these variables into our analysis and evaluate their roles in the comovement of regional business cycles. Our findings indicate two major results: First, low degree of synchronization during 1975-2000 has switched to relatively more correlated and synchronously moving regional cycles during 2004-2010. Second, having tested the variety of determinants, we find that the pairs of regions that have more similar industrial structure and market size, and arbitrary degree of agglomeration and urbanization tend to synchronize more. Significance of these variables is robustly evident regardless of the time period analyzed and of the type of methodology employed.
Keywords: E32; E63; R11; 330; Regional Business Cycles; Synchronization; Agglomeration; Industrial Dissimilarity